The Development of LITTLECARE: Childcare Management System Using Laravel Framework - Saahari, Intan Nur Fatiha; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2025)
Manual handling of childcare operations at Taska Hikmah, Batu Pahat, often leads to inaccuracies, inefficient data management, and lack of real-time children monitoring. This study aims to develop and evaluate LITTLECARE: Childcare Management System to automate attendance tracking, daily event updates, billing processes and provide real-time monitoring for administrators, staff and parents. The system was designed through a structured development approach with the prototyping model, and it used Laravel as the backend framework, HTML, CSS, and JavaScript for the frontend, and MySQL for data storage. The system was evaluated through alpha beta testing. User Acceptance Testing evidence displayed high satisfaction among 90% of respondents, confirming the system success in solving the inefficiencies of childcare operation management. The system significantly increased data accuracy and overall efficiency, including suggestions for the future to integrate into mobile applications along with deriving AI-driven perceptions to allow better safety measures to enhance user experience and accessibility.